Islamic Entrepreneurship: A Systematic Review Of Future Challenges And Prospects Of Pakistani SMEs - Muhammad Khalique; T. Ramayah; Khushbakht Hina; Jamal Abdul Nassir Shaari (International Islamic University Malaysia (IIUM), 2024)
The main objective of this study is to provide a framework of Islāmic entrepreneurship for Pakistani SMEs to address their issues within a knowledge-based economy perspective. The paper reviews contemporary literature and the Holy Qurʾān verses, the Prophet Muhammad’s (ṣal-Allāhu ʿalayhi wa sallam) Hadīth(sayings) and Sunnah(practice)on Islāmic entrepreneurship, for establishing a business model for entrepreneurs. On the basis of extensive literature reviews and evidence, the study proposed a business model of Islāmic entrepreneurship which is mainly based on two dimensions namely business perspective and spiritual perspective. The paper is conceptual in nature. There is a need for developing a measurement scale to measure the business model of Islāmic entrepreneurship .Islāmic entrepreneurship is considered as the most crucial topic in business solutions because of the very complex and dynamic business environment. In the present business environment, the role of religion and culture is very important for the success of SMEs. The proposed business model of Islāmic entrepreneurship will help Pakistani SMEs to understand the halal and haram concept in more depth. Moreover, they would be able to capitalize the Islāmic rules and principles in their business. The novelty of this study lies in expanding the existing research on the link between Islāmic entrepreneurship and the future challenges and prospects of Pakistani SMEs. The proposed business model of Islāmic entrepreneurship is unique and it will guide development of the scale to measure Islāmic entrepreneurship in organizations. This is arguably a first study contributing to Islāmic entrepreneurship literature in the Pakistani context.